Peran Kompetensi Dan Transparansi Dalam Mempengaruhi Pengendalian Tindakan Fraud Pengelolaan Dana Desa - Faris Rahmawan; Fajar Syaiful Akbar (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to determine whether there is a relationship between competence, organizational commitment and transparency on fraud prevention in village fund management. Quantitative methodology is used to test whether there is a relationship between variables and to collect primary data through questionnaires or surveys of all village officials in Palang District. The population in this study amounted to 197 people. The sampling method used was purposive sampling, namely the selection of data samples with certain conditions. Samples were selected through indicators of Tuban Regent Regulation No. 29 of 2017, namely village officials who have an understanding and role related to finance and fraud detection in realizing, managing and budgeting village funds. From the sampling method, the respondents in this study amounted to 72 officials, namely 4 village officials each from 18 villages, namely the village head, village secretary, finance head, and welfare head in Palang sub-district. To assist in analyzing multiple liner regression using SPSS version 26. The results showed that competence and organizational commitment did not have a significant effect but transparency had a significant effect on preventing fraud in the management of village funds in Palang District, Tuban Regency